Burn out and depression in paramedical workers of tertiary care hospital during COVID-19 pandemic - Kanwar, Neeraj; Lal, Roshan; Kumar, Ramesh (International Journal of Research in Medical Sciences, 2022)
Background: Medical/paramedical professionals are prone to various behavioral disorders due to work pressure. The aim of the study was to evaluate burnout and depression in paramedical workers of a tertiary care hospital during COVID-19. Methods: Paramedical health care workers were assessed using online questionnaire containing self-administered questionnaire in this cross-sectional study between March 2021 and May 2021. Burnout self-test, depression, and anxiety were measured. Results: In this study, only 2.6% had at very severe risk of burnout and 7.8% were at severe risk of burnout while 3.9% had no signs of burnout. Approximately 80% of the patients had no depression. While there were 19.5% had mild to severe depression. Only eight out of 77 subjects had clinically significant symptoms of anxiety. Two subjects were having comorbid illness. Conclusions: A considerable percentage of HCWs experience burnout, depression, and anxiety.